STRUKTUR KEPEMILIKAN, KEBIJAKAN HUTANG DAN NILAI PERUSAHAAN : KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERATING - Eka Mira Rismayanti; Yusralaini Yusralaini; Devi Safitri (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2020)
The purpose of this research were to analyze the effect of managerial ownership, institutional ownership and debt policy of the fims value with dividend policy as moderation. Population on this research is all companies listed in IDX 2015-2017. This research sample selected by using the purposive sampling method, there are 228 sample. The analysis method of this research is multiple regression analysis and moderated regression analysis while hypothesis tested by using SPSS 25. The result of this research shows that: managerial ownership has negative effect on firm value. Institutional ownership has an effect on firm value. Debt policy has no effect on firm value. Dividend policy is able to moderated the relationship between managerial ownership and firm value. Dividend policy is able to moderated the relationship between institutional ownership and firm value. Dividend policy is not able to moderated the relationship between debt policy and firm value.